Tensile Properties and Impact Toughness of AlCoxCrFeNi3.1–x (x = 0.4, 1) High-Entropy Alloys - Zhang, Lu; Zhang, Yong (Frontiers in Materials, 2020)
AlCoxCrFeNi3.1-x high-entropy alloys (HEAs) with different cobalt and nickel contents (i.e., x values in molar ratio, where x = 0.4, 1) are initially prepared by using vacuum induction melting. These two HEAs, AlCo0.4CrFeNi2.7 and AlCoCrFeNi2.1, both form FCC+B2 structure. The tensile tests and impact tests with V-notch and U-notch (at 77 K, 200 K and 298 K) were carried out. It can be known from the experiments that the tensile properties of them are similar with each other, whose yield strength, fracture strength and elongation are ~540 MPa, ~1000 MPa and ~10%, respectively. While there is a little different between the impact properties. The impact energy of AlCo0.4CrFeNi2.7 is 21.77 J at 298 K, which is more than three times as much as AlCoCrFeNi2.1. Compared with Al0.3CoCrFeNi and Al0.1CoCrFeNi FCC structured HEAs, AlCoxCrFeNi3.1-x alloys show low impact toughness but high yield strength.